2023
DOI: 10.3390/pharmaceutics15010164
|View full text |Cite
|
Sign up to set email alerts
|

Nanoemulgel: A Novel Nano Carrier as a Tool for Topical Drug Delivery

Abstract: Nano-emulgel is an emerging drug delivery system intended to enhance the therapeutic profile of lipophilic drugs. Lipophilic formulations have a variety of limitations, which includes poor solubility, unpredictable absorption, and low oral bioavailability. Nano-emulgel, an amalgamated preparation of different systems aims to deal with these limitations. The novel system prepared by the incorporation of nano-emulsion into gel improves stability and enables drug delivery for both immediate and controlled release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 151 publications
0
18
0
Order By: Relevance
“…Despite this, it also provides high drug loading, better drug diffusion, biocompatibility, and minimized irritancy. 35 The current study reported ketoconazole-loaded NEGs based on clove oil (clove-oil−NEG) and eucalyptus oil (eucalyptusoil−NEG) in the gelling agent carbopol 943 and HPMC for improved therapy against candidiasis. An extensive preformulation study was performed on the API and their physicochemical properties for developing a robust, stable, and effective dosage form.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, it also provides high drug loading, better drug diffusion, biocompatibility, and minimized irritancy. 35 The current study reported ketoconazole-loaded NEGs based on clove oil (clove-oil−NEG) and eucalyptus oil (eucalyptusoil−NEG) in the gelling agent carbopol 943 and HPMC for improved therapy against candidiasis. An extensive preformulation study was performed on the API and their physicochemical properties for developing a robust, stable, and effective dosage form.…”
Section: Discussionmentioning
confidence: 99%
“…Nanoemulgel protects medicament from enzymatic degradation and hydrolysis and improves retention and skin permeation. Despite this, it also provides high drug loading, better drug diffusion, biocompatibility, and minimized irritancy …”
Section: Discussionmentioning
confidence: 99%
“…Bio-polysaccharides or their derivatives and proteins belong to natural gelling agents. For instance, bio-polysaccharides are pectin, carrageenan, alginic acid, and gelatin, whilst xanthan gum, starch, and dextran are derivatives of bio-polysaccharides [ 34 ]. However, various kinds of both semi-synthetic and synthetic gelling agents are widely used in emulgel formulation [ 5 ].…”
Section: Formulation Of Emulgelmentioning
confidence: 99%
“…To address these limitations, an emulsion-loaded gel can be used to incorporate and deliver a hydrophobic therapeutic moiety via a topical route. Emulgels are dosage forms produced by combining emulsions and gels, possess high penetration capacity, elegance after application, and can easily be wiped off from the skin [ 23 ]. Emulgels for dermatological use have several advantages, including having thixotropic behavior, acting as an emollient, having a longer shelf life, high drug loading capacity, exhibiting controlled release, and improving stability [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%